Meningkatkan Hasil Pembelajaran PKn dengan Metode Detektif (Debat Secara Aktif) pada Materi Budaya Demokrasi pada Siswa Kelas XI – IPA1 SMAN 14 Semarang Tahun Pelajaran 2016-2017 (Integralistik, 2019)
Civic of senior high school is not a subject that attract the students. Besides that, there are some reason why students’ KKM scores are bellow the other subjects’ score. At least, students aren’t active during the lesson. Often, a teacher is not putting the highest the effort while using novel educational media and the most important is, the teacher is not courageous enough to apply innovative model of lesson leading. Based on previous experience when the students were passive, teaching civics in Budaya Demokrasi at XI – IPS 1 SMAN 14 Semarang requires a special handling from the teacher.     Based on our research, debate method that the ones method at discussion is very important to improve students’ academic abilities. The kind of this research which was conducted in two cycles, to enchance their creativity and improve their grade score in civics.The result show that after 2 cycles accompained with teachers’ reflection ther was an increase of proportion of students who passed the average grade in 2 variables, enthusiasm to study and activity during civics lesson. With culivate the descriptif of data for amount of students’ who complete increase in  variable 98% and 100%. And the activity during lessons increased to 80% and 100%. The echancement come about students’ academic score. The grade score on first cycle and second cycle increased to average score of 79,56% and 84,72%. Percentage of completeness of students’ score in particular in first cycle and two is 80% and 100%.With the result, we can conclude that the debate methode can be used to improve the activity and ability of students to understand concept of problem solving education in the civics in class XI – IPS 1 SMAN 14 Semarang.Although intially the students experience is awkward in expressing their opinion on debate method, in the end the student adapted and got achievements based on the good result.